Perlindungan Hukum terhadap Trenggiling (Manis Javanica) Penjaga Hutan yang Terus Diburu - Bambang Ari Wibowo (Jurnal Hukum dan Sosial Politik, 2026)
The Sunda pangolin (Manis javanica) is an important ecological species that contributes to ecosystem balance. However, its population faces serious threats from hunting, habitat destruction, and illegal wildlife trade. The high economic value of pangolin meat and scales, combined with beliefs about their medicinal benefits, has driven continued exploitation. This condition demonstrates that pangolin conservation involves not only ecological concerns but also legal protection and law enforcement challenges. This study aims to analyze the legal protection of the Sunda pangolin in Indonesia and identify challenges in enforcing laws against illegal hunting and trade. This research employs a normative juridical method using statutory and conceptual approaches, supported by empirical data from observations, interviews, and case-handling information. The findings show that pangolin protection is supported by strong national and international legal frameworks. The Sunda pangolin is classified as a protected species under Indonesian conservation regulations and listed in Appendix I of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Its legal protection has also been strengthened through Law Number 32 of 2024, amending Law Number 5 of 1990. Nevertheless, enforcement remains challenged by high market demand, economic incentives, public beliefs, and complex trafficking networks. Therefore, protection should be strengthened through evidence-based investigations, trade-route monitoring, wildlife forensics, international cooperation, and public awareness and participation in conservation.